Peningkatan Pemasaran Melalui Pembuatan Kue Cumcum Aneka Rasa pada Usaha Roti dan Kue Kampung Tajung di Kelurahan Polagan Kabupaten Sampang - Adiananda Adiananda; Tri Wardoyo; Achmad Yulianto; Amirullah Amirullah (Semar: Jurnal Pengabdian Kepada Masyarakat, 2026)
PKM partners are the Tajung Village Bread and Cake Micro Business. Partner problems include production, management, and marketing aspects. The production problem is that the partner's flagship product, mini cumcum cake, only consists of two flavors, namely chocolate and vanilla. The management problem is that recording or financial administration (cash) for cake sales and purchasing ingredients is still done manually. The marketing problem is that increasing cake marketing turnover is still limited when approaching the fasting month and Eid. The objectives of implementing the activity are: (1) increasing knowledge and skills in making mini cumcum cakes with cheese, green tea, melon, taro, and strawberry flavors, (2) increasing knowledge regarding production management and financial administration processes so that the business is more efficient starting from the phase of purchasing ingredients, stock of ingredients, production, stock of finished goods, promotion, to selling cakes, and (3) increasing knowledge and skills in creating online promotional content for cake products through social media. The output of the activity is The results of the activity are (1) mini cumcum cake products with alternative flavors: cheese, green tea, melon, taro, and strawberry, (2) documents for production management and financial administration processes, and (3) online promotional content for cake products through social media (Facebook and Instagram).